1998
DOI: 10.1093/jnci/90.13.1000
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Bone Sialoprotein Expression in Clinically Localized Human Prostate Cancer

Abstract: To our knowledge, this study is the first to demonstrate BSP expression in human prostate cancer and to highlight the protein's statistically significant prognostic value in patients with clinically confined prostate adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
111
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(116 citation statements)
references
References 33 publications
2
111
1
2
Order By: Relevance
“…However, little progress has been made in understanding the molecular mechanisms responsible for bone metastasis in prostate cancer. Our lab and others found that noncollagenous bone matrix proteins such as osteopontin, OC, and bone sialoprotein are expressed at high levels in advanced bone metastatic prostate tumor specimens (33)(34)(35) and AI bone metastatic prostate cancer cell lines. There seems to be a remarkable parallelism in the temporal expression of bone matrix proteins by prostate cancer cells and mature osteoblasts.…”
Section: Discussionmentioning
confidence: 67%
“…However, little progress has been made in understanding the molecular mechanisms responsible for bone metastasis in prostate cancer. Our lab and others found that noncollagenous bone matrix proteins such as osteopontin, OC, and bone sialoprotein are expressed at high levels in advanced bone metastatic prostate tumor specimens (33)(34)(35) and AI bone metastatic prostate cancer cell lines. There seems to be a remarkable parallelism in the temporal expression of bone matrix proteins by prostate cancer cells and mature osteoblasts.…”
Section: Discussionmentioning
confidence: 67%
“…[28][29][30] They are secreted by certain tumor cells with metastatic affinity to bone tissue, as for example by breast, prostate, lung and other cancer cells. 2,3,12,13,18,[31][32][33][34] In addition, they show various functions; OPN can bind to a number of receptors such as integrins as well as to certain variant forms of CD44, [35][36][37] it can act as a cytokine 29 and has function in the urinary tract. 31 BSPII is closely related to OPN, 38,9 but ON differs from OPN and BSPII by its chromosomal origin, its lack in an RGD binding domain, and its function that is related for example to the maintenance of lens transparency as has been described in knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…9 These proteins often function by bridging two proteins of fixed structures into a biologically active complex. The structural similarity of BSPII with OPN is paralleled by the observation that both proteins are expressed by certain tumor cells such as breast cancer, 10,11 as well as colon, prostate 12 and lung cancer, 13 and have been related to the pathogenesis of bone metastasis. 8 The calcium binding properties of BSPII 14 and its role in initiating and controlling hydroxylapatite crystallization 15 have been related to the formation of microcalcification in breast cancer.…”
mentioning
confidence: 97%
“…In breast and prostate cancer, the expression of BSP has already been shown to be highly predictive of neoplastic bone involvement (Bellachène et al, 1996a;Waltregny et al, 1998;Diel et al, 1999). In these cancers, as well as in myeloma, the interaction between tumour cells and osteoclasts seems to be pivotal for the growth and propagation of the neoplastic cell clone in the bone marrow and for the subsequent bone destruction (Mundy and Yoneda, 1998).…”
Section: Discussionmentioning
confidence: 99%